Good riddance ebook - Lipman, Elinor (2019)
In a delightful new romantic comedy from Elinor Lipman, one woman's trash becomes another woman's treasure, with deliriously entertaining results. Daphne Maritch doesn't quite know what to make of the heavily annotated high school yearbook she inherits from her mother, who held this relic dear. Too dear. The late June Winter Maritch was the teacher to whom the class of '68 had dedicated its yearbook, and in turn she went on to attend every reunion, scribbling notes and observations after each one—not always charitably—and noting who overstepped boundaries of many kinds. In a fit of decluttering (the yearbook did not, Daphne concluded, "spark joy"), she discards it when she moves to a small New York City apartment. But when it's found in the recycling bin by a busybody neighbor/documentary filmmaker, the yearbook's mysteries—not to mention her own family's—take on a whole new urgency, and Daphne finds herself entangled in a series of events both poignant and absurd. Good Riddance is a pitch-perfect, whip-smart new novel from an "enchanting, infinitely witty yet serious, exceptionally intelligent, wholly original, and Austen-like stylist" (Washington Post).